1992
DOI: 10.1128/aac.36.12.2611
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin or teicoplanin in combination with gentamicin for treatment of experimental endocarditis due to a highly glycopeptide-resistant isolate of Enterococcus faecium

Abstract: Using an experimental endocarditis model, we studied the activity of daptomycin used alone or in combination with gentamicin against an Enterococcusfaecium strain that was highly resistant to glycopeptides and susceptible to gentamicin. In vitro, the MIC of daptomycin was 1 ,ug/ml. In vivo, daptomycin appeared to be effective only when it was used in a high-dose regimen, i.e., 12 mg/kg of body weight every 8 h (-2.5 log1o CFU/g versus controls; P < 0.05), particularly when it was combined with gentamicin (-5.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 17 publications
1
38
0
2
Order By: Relevance
“…This is due to the mechanism of action of daptomycin: it disrupts the cell membrane potential and is growth phase independent (8). There are promising data demonstrating in vitro synergy for gentamicin-and-daptomycin combination therapy against vancomycin-resistant enterococci (VRE) (9)(10)(11)(12)(13), and case reports also support these findings (11,14,15). Therefore, the addition of gentamicin, a ribosomal active agent, may provide a synergistic approach to VRE IE infections.…”
mentioning
confidence: 56%
“…This is due to the mechanism of action of daptomycin: it disrupts the cell membrane potential and is growth phase independent (8). There are promising data demonstrating in vitro synergy for gentamicin-and-daptomycin combination therapy against vancomycin-resistant enterococci (VRE) (9)(10)(11)(12)(13), and case reports also support these findings (11,14,15). Therefore, the addition of gentamicin, a ribosomal active agent, may provide a synergistic approach to VRE IE infections.…”
mentioning
confidence: 56%
“…This is consistent with the results of previous studies, in which daptomycin was found to be active against GISA isolates. The results of animal model experiments for determination of the efficacy of daptomycin against IE infections caused by enterococci (6,24), as well as S. aureus and MRSA (5,30), have previously been published in the peer-reviewed literature, but there are limited data from animal models on its efficacy against GISA IE infections (23). The present study used a rabbit model simulating human-like PKs to investigate the efficacy of daptomycin against aortic valve IE caused by MRSA or GISA.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative autoradiography showed daptomycin to be homogenously distributed throughout the vegetations (8).…”
mentioning
confidence: 99%